Cutting performance improvement of MTCVD coated cemented carbide inserts via appropriate heat treatment. Issue 1 (2020) - Skordaris, G.; Bouzakis, K.D.; Stergioudi, F.; Kouparanis, S.; Boumpakis, A.; Bouzakis, A.
Abstract: The softening of cemented carbide at the elevated temperature of MTCVD processes results in significant reduction of their strength, and thus, high coating deformation during cutting. In this way, at interrupted cutting loads, as during turning cast iron, the cutting performance of MTCVD coated cemented carbide inserts degrades due to premature coating fatigue fracture. To overcome this problem, appropriate heat treatments of MTCVD coated inserts were conducted. The related temperatures and durations for improving the substrate properties were optimized considering obtained strength data of uncoated inserts variously heat treated and the turning performance of coated ones correspondingly heat treated.